PENGARUH KUALITAS PELAYANAN, REPUTASI PERUSAHAAN, DAN ATRIBUT PERUSAHAAN TERHADAP MINAT BELI ULANG PENGGUNA GO-FOOD YOGYAKARTA - galih pradiantoro galih pradiantoro (JURNAL EKOBIS DEWANTARA, 2018)
The research is aimed to explore the effect of the service quality, the reputation of company, and the attribute of company toward the repurchase intention of go-food customers at Yogyakarta. This research is using the questionnaire form which is dispersed as the premier data. Population in this research is the common people costumer who has go-jek application and has used go-food's service at Yogyakarta, while the sample in this research is the common people costumer who has used go-food's service at least twice at Yogyakarta city when this research is done. The result of research reveals the reality effect of the effect of the service quality, the reputation of company, and the attribute of company toward the repurchase intention of go-food customers at Yogyakarta. keywords: service quality, reputation of company, attribute of company, and repurchase intention